KNOWLEDGE MANAGEMENT IN VIRTUAL COMMUNITY OF PRACTICE (VCoP) - Mahesa Rani, Putu; Salim, Tamara Adriani; Wibowo, Muhammad Prabu (Universitas Mataram, 2024)
Knowledge Management (KM) is essential for organizations to remain competitive and innovative in today's rapidly evolving global landscape. Virtual Communities of Practice (VCoPs) have emerged as valuable platforms for knowledge sharing and collaboration among individuals with common professional interests. The purpose of this research is to analyze how knowledge develops in virtual communities of practice based on the SECI concept by Nonaka Takeuchi. The data comes from any scientific paper about the implementation of KM in VCoPs in several fields from 2017 until 2023. This research utilized a Systematic Literature Review (SLR) based on the PICOC methodology. This systematic literature review observes and identifies KM implementation through its knowledge conversion concept. The result show that Socialization process in virtual spaces are crucial for overcoming barriers like distance and time, allowing continuous knowledge sharing even outside regular working hours. Externalization process facilitate the sharing of relevant professional knowledge, including stories, concepts, videos, or images related to daily work experiences. In the Combination process, there are differences between one VCoP and another because it is influenced by the online/virtual media used. Internalization as sustainability of knowledge sharing processes, especially related to mentoring, varies across different VCoPs. The conclusion is while KM have become integral for VcoPs, challenges such as platform limitations and varying success in implementing knowledge sharing processes exist.